A Comparative Study of the Motives of KHAT in the poetical works of Naziri and collection of lyric poems of Saâeb - عصمت اسماعیلی (مطالعات زبانی و بلاغی)
One of the elements of fantasy poses and meaning construction in the poetry of the new style poets or Indian style, are the Motives. The key words of meaning construction, which get situated in the centre of language and communication network, and associated with the concept of language and vocabulary, while using parallelism and the narrow sense of the poet, lead to a very effective lyric discussion with the audience, especially in the lyric type of poems. In the poetical works of Naziri Neyshaburi, some descriptive combinations and words get out of the circle of their ordinary dictionary meanings and being placed in the centre of the language networks, help the poet, in order to creation of innovative concepts, they also transfer their cognitive concepts to the reader&#39s mind. For instance, words like: sepehr with 51 or khat with 74, khak with 166 or ka’be with 125 different usages in his poems- have helped the poet in constructing differentiated meanings. In this article, I try to compare the motives of khat in the poetical works of Naziri and Sa’eb, while referring to some motives used in the poetical works of Naziri.